Exploring interconnections in SCM body of knowledge - Crespo de Carvalho, J.; Guimarães, C.; Martins, A. (Journal of Management and Strategy, 2014)
This paper aims at contributing to new insights and ideas in the area of Supply Chain Management. Revisiting some theories and areas of knowledge is critical to generate different perspectives and ways of understanding supply chains. Accordingly, this paper reopens some areas of knowledge that have fed and are continuing to feed the area of SCM (Supply Chain Management) with new ideas and thoughts, in both theoretical and practical terms. SCM approaches and practices are cross functional, organizational and inter-organizational centred areas of knowledge and, for these reasons, the authors have also made an effort to dedicate some parts of the paper to discuss and register some competitive advantages arising essentially from a pre-paradigmatic body of knowledge like SCM.